A novel sensitive assay for detection of a biomarker of pericyte injury in cerebrospinal fluid. Issue 6 (16th April 2020) - Sweeney, Melanie D.; Sagare, Abhay P.; Pachicano, Maricarmen; Harrington, Michael G.; Joe, Elizabeth; Chui, Helena C.; Schneider, Lon S.; Montagne, Axel; Ringman, John M.; Fagan, Anne M.; Morris, John C.; Pa, Judy; et al.
Abstract: Introduction: Blood‐brain barrier (BBB) breakdown and loss of brain capillary pericytes contributes to cognitive impairment. Pericytes express platelet‐derived growth factor receptor‐β (PDGFRβ) that regulates brain angiogenesis and blood vessel stability. Elevated soluble PDGFRβ (sPDGFRβ) levels in cerebrospinal fluid (CSF) indicate pericyte injury and BBB breakdown, which is an early biomarker of human cognitive dysfunction. Methods: A combination of reagents and conditions were tested, optimized, and validated on the Meso Scale Discovery electrochemiluminescence platform to develop a new sPDGFRβ immunoassay that was used to measure sPDGFRβ in human CSF from 147 individuals. Results: We developed standard operating procedures for a highly sensitive and reproducible sPDGFRβ immunoassay with a dynamic range from 100 to 26, 000 pg/mL, and confirmed elevated CSF sPDGFRβ levels in individuals with cognitive dysfunction. Discussion: This assay could be applied at different laboratories to study brain pericytes and microvascular damage in relation to cognition in disorders associated with neurovascular and cognitive dysfunction.